Efektifitas Pendidikan Kesehatan Vagina Hygiene Tentang Keputihan Terhadap Pengetahuan dan Sikap Remaja di SMK Kesehatan Bantul - Wulandari, Baiq Rina; Fatimah, Fatimah; Pangestuti, Restu; Paramita, Dyah Pradnya; Mulyaningsih, Sundari (Borobudur Nursing Review, 2024)
Background: WHO states that 5% of teenagers in the world are infected with sexually transmitted diseases with symptoms of vaginal discharge every year. In Indonesia, as many as 90% of women experience vaginal discharge and as many as 60% are experienced by teenage girls. Adolescents who are in a transitional period, accompanied by the maturity of their reproductive organs, need special attention. This study aims to determine the effectiveness of vaginal hygiene health education on the knowledge and attitudes of adolescents at the Bantul Health Vocational School. Objective: To determine the effectiveness of vaginal hygiene health education on the knowledge and attitudes of Bantul Health High School students. Research Method: Research was conducted in February – March 2023 at Bantul Health Vocational School. This type of research is Quasi Experimental research with a Pretest and Posttest Design with a sample size of 30 people consisting of class XII female students. Sampling was taken using total sampling technique. Data collection was carried out using Pretest and Posttest questionnaires. Data were analyzed using the Shapiro Wilk Normality test because the amount of data in each group was lower than 50 and the Wilcoxson test because the results of the normality test showed that the data was not normally distributed. Results: 1) Before being given education, students' knowledge was 0.061 (significant p>0.05), indicating that the data was normally distributed, and after being given education, knowledge was 0.007 (significant p<0.05), indicating that the data was not normally distributed. Meanwhile, students' attitudes before being given education was 0.028 (significant p<0.05) indicating the data was not normally distributed and after being given education was 0.000 (significant p<0.05) indicating data was not normally distributed 2) There was a difference in knowledge before and after being given education of 0.000 (significant p<0.05) 3) There is a difference in attitudes before and after being given education of 0.030 (significant p<0.05). So it shows that there is a correlation between treatment in the form of Vaginal Hygiene Health Education and the knowledge and attitudes of teenagers at the Bantul Health Vocational School. Conclusion: there are differences in the knowledge and attitudes of Bantul Health High School students before and after being given education. Based on the results of this research, researchers suggest that female students should increase their insight and knowledge regarding reproductive health, including attitudes about vaginal hygiene, in order to improve reproductive health.